Study on the Coevolution Mechanism of Slope and Prevention Structures under Rainfall. (4th May 2022) - Tang, Lin; Wu, Daoyong; Wu, Honggang; Wei, Hong; Pang, Jun; Guan, Wei; Sun, Hao
Abstract : The relationship between slope and prevention structures under the action of rainfall is complicated. In this paper, a series of model tests were carried out to study the coevolution mechanism of slope and prevention structures under rainfall. It was found that the prestressed grouting steel anchor tube frame beam composite structure has a good reinforcement and protective effect on the slope. Specifically, less damage degree is observed for a slope with prestressed grouting steel anchor tube frame beam, while the slope of without prestressed grouting steel anchor tube frame beam suffers from severe deformation. Under the effect of rainfall, the evolution process of slope and prevention structure cooperative deformation can be divided into three stages: creep stage, extrusion stage, and acceleration stage. The antisliding force provided by the prevention structure is positively correlated with the slope deformation. Moreover, as an initiating factor for changes in various monitoring parameters, rainfall plays a dominant role in the variation of earth pressure reinforcement by steel anchor tube.